Commercial appropriation of personality - Beverley-Smith, Huw (Cambridge studies in intellectual property rights., 2002)
Beverley-Smith provides analyses of the disparate aspects of commercial appropriation of personality and traces, in detail, the discrete patterns of development in the major common law systems. He also considers whether a coherent justification for a new remedy may be identified from a range of competing theories.